Chest Radiographic Findings and Outcomes of Pneumonia Among Children in Botswana. Issue 3 (March 2016) - Kelly, Matthew S.; Crotty, Eric J.; Rattan, Mantosh S.; Wirth, Kathleen E.; Steenhoff, Andrew P.; Cunningham, Coleen K.; Arscott-Mills, Tonya; Boiditswe, Sefelani; Chimfwembe, David; David, Thuso; Finalle, Rodney; Feemster, Kristen A.; et al.
Abstract : Background: Chest radiography is increasingly used to diagnose pneumonia in low-income and middle-income countries. Few studies examined whether chest radiographic findings predict outcomes of children with clinically suspected pneumonia in these settings. Methods: This is a hospital-based, prospective cohort study of children 1–23 months of age meeting clinical criteria for pneumonia in Botswana. Chest radiographs were reviewed by 2 pediatric radiologists to generate a consensus interpretation using standardized World Health Organization criteria. We assessed whether final chest radiograph classification was associated with our primary outcome, treatment failure at 48 hours, and secondary outcomes. Results: From April 2012 to November 2014, we enrolled 249 children with evaluable chest radiographs. Median age was 6.1 months, and 58% were male. Chest radiograph classifications were primary endpoint pneumonia (35%), other infiltrate/abnormality (42%) or no significant pathology (22%). The prevalence of endpoint consolidation was higher in children with HIV infection ( P = 0.0005), whereas endpoint pleural effusions were more frequent among children with moderate or severe malnutrition ( P = 0.0003). Ninety-one (37%) children failed treatment, and 12 (4.8%) children died. Primary endpoint pneumonia was associated with an increased risk of treatment failure at 48 hours ( P = 0.002), a requirement for more days of respiratory support ( P = 0.002) and a longer length of stay ( P = 0.0003) compared with no significant pathology. Primary endpoint pneumonia also predicted a higher risk of treatment failure than other infiltrate/abnormality ( P = 0.004). Conclusions: Chest radiograph provides useful prognostic information for children meeting clinical criteria for pneumonia in Botswana. These findings highlight the potential benefit of expanded global access to diagnostic radiology services.